Strategy for Increasing Competence of Medical Representatives - Baskoro Hidayatullah, Agung; Thomas, Partono; Widiyanto, Widiyanto (Journal of Economic Education, 2020)
Graduates of the marketing expertise competency at the SMK Pharmasi Semarang Foundation are not in accordance with the competencies required by the Business World and the Industrial World (DUDI) as a medical representative. The purpose of this study was to analyze the strategy for increasing medical representative competency in terms of learning, collaboration with DUDI, and human resource development (teachers). This research uses descriptive qualitative research with data collection techniques of observation, interviews, documentation, and triangulation then the data is reduced. The strategy to increase medical representative competence is carried out through practical learning by conducting simulation learning in the learning process inside and outside of school. Learning conducted in schools focuses on practical simulations to sharpen student competencies in communicating with doctors and understand products to be promoted through industry-based learning. Non-school learning is carried out through a collaboration program between school agencies and DUDI in the form of fieldwork practices by adjusting the implementation time of the apprenticeship with the allocation of concept time for pharmaceutical sales. Achievement of medical representative competencies for marketing students is supported by teacher competency. Teacher competence in the field of medical representative is obtained through the on the job training program.